Torque and Power Characteristics of Single Piston LPG-Fueled Engines on Variations of Ignition Timing - Bagiyo Condro Purnomo; Noto Widodo (Universitas Muhammadiyah Magelang, 2019)
Liquefied Petroleum Gas (LPG) is an alternative fuel that has all key properties for the Spark Ignition (SI) engine. However, because of its properties, ignition timing on an LPG SI engine needs to be advanced from the reference angle to get the optimum performance. Therefore, this article presents the torque and power characteristics of a single piston LPG engine on variations of ignition timing. Evaluation of engine performance is carried out at the ignition timing of 15O, 17O, and 19O BTDC. The results showed the highest torque for LPG fuel was 10.64 Nm which was achieved at 3500 rpm with ignition timing of 19O BTDC, while the highest power for LPG fuel was 6.9 hp which was achieved at 5936 rpm with ignition timing of 19O BTDC.